Determination of calcium leaching behavior of cement pastes exposed to ammonium chloride aqueous solution via an electrochemical impedance spectroscopic approach. (30th January 2019) - Song, Zijian; Liu, Yongqi; Jiang, Linhua; Guo, Mingzhi; Chen, Jianguo; Wang, Wanyi; Xu, Na
Highlights: Electrochemical impedance spectroscopy is applied to evaluate the leaching behavior. A new electrical equivalent circuit is proposed to extract parameters from impedance spectra. A linear relationship between xL and R′CCP is suggested to quantify the leaching depth. Abstract: This study employed EIS (electrochemical impedance spectroscopy) as a non-destructive method to study the leaching behavior of the cementitious materials subjected to aggressive environments. A novel electrical equivalent circuit was established based on a microstructure assumption concerning the leaching-induced degradation. Electrochemical parameters were extracted from the impedance spectra by fitting the established equivalent circuit. On the basis of the understanding of the physical meanings, a proper equivalent-circuit parameter was defined as the indicator of leaching depth. Then the relationship between the leaching depth and the indicator was estimated. As a result, leaching depths can be quantitatively estimated using EIS method.